A bio-based ultraviolet-thermal dual-curing coating with high hardness, wear resistance and thick coating and a preparation method thereof

CN122941277APending Publication Date: 2026-10-20SICHUAN FANHUA AVIATION INSTR & ELECTRICAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611315814.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

(1)阴影固化问题:传统的紫外光固化涂料因固化特性,通常只能薄涂(一般<100μm),且主要适用于平面或简单形状

Benefits of technology

(1)本发明通过生物基紫外光固化低聚物、活性单体与无机填料的复配,以及紫外光固化与热引发的“点击化学”反应的结合(底层彻底固化),涂层具有高硬度、高耐磨和可厚涂等三大核心性能,本发明的储存稳定性好:所选热潜伏性固化剂在室温下不发生反应,确保了涂料具有至少12个月的储存期。本发明具有生物基含量高、固化效率高的优点,可以适用于厚涂施工,实现了深层彻底固化与优异机械性能的统一,具有较好的实用性。具体地,本发明具有卓越的厚涂与深固化能力,完美解决了复杂工件和厚涂层的固化难题。可实现单次涂布150-300μm的干膜厚度而不开裂、不发粘。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

This invention discloses a high-hardness, wear-resistant, and thick-coatable bio-based UV-thermal dual-curing coating and its preparation method, belonging to the technical field of UV-curable coatings. The cured coating, by weight, comprises: 30-50 parts of bio-based UV-curable oligomer, 20-40 parts of reactive diluent, 2-5 parts of photoinitiator, 5-15 parts of thermally latent curing agent, 5-20 parts of functional inorganic filler, and 0.5-2 parts of additives. The bio-based UV-curable oligomer is a castor oil-based maleic acid half-ester modified epoxy acrylate; the thermally latent curing agent comprises end-capped isocyanate and thiol compound, with a molar ratio of 1:1 to 1:1.2. This invention has the advantages of high bio-based content and high curing efficiency, and can be applied to thick coating construction, achieving a balance between deep and thorough curing and excellent mechanical properties, thus possessing good practicality.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the technical field of ultraviolet (UV) curable coatings, specifically relating to a high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curable coating and its preparation method. Background Technology

[0002] UV-curable coatings are widely used in wood, plastics, paper, and metal coatings due to their advantages such as fast curing speed, low energy consumption, and low VOC (volatile organic compound) emissions. However, traditional UV-curable coatings face the following technical bottlenecks: (1) Shadow curing problem: Due to their curing characteristics, traditional UV-curable coatings can usually only be applied in thin layers (generally <100μm) and are mainly suitable for flat or simple shapes. For workpieces with complex shapes or thick coatings, UV light is difficult to reach the underlying layer, resulting in insufficient curing of the underlying layer, stickiness of the coating, and decreased performance. At present, in order to solve the shadow curing problem, dual curing systems have been introduced in existing technologies, such as UV light-heat and UV light-humidity. However, existing dual curing coatings usually have problems such as poor system compatibility, high internal stress of the cured coating, and low bio-based content.

[0003] (2) Thick coating limitation: When the coating is too thick at one time, the surface layer will solidify rapidly, which will hinder oxygen inhibition, but at the same time, it will limit the thickness of a single coating and affect production efficiency.

[0004] (3) Raw material dependence on petrochemical resources: The resins and reactive diluents of traditional UV-curable coatings are mostly derived from petroleum. The main film-forming material of traditional UV-curable coatings is acrylate oligomers, which are mostly derived from non-renewable petroleum resources and do not meet the requirements of sustainable development. For example, the commonly used UV-thermal dual-curing coatings mainly rely on amino resins for their thermal curing part, which poses a potential risk of formaldehyde release and does not solve the problem of internal stress caused by thick coatings.

[0005] (4) Balance between hardness and toughness: Although traditional UV-cured coatings have high hardness, they are brittle and prone to shrinkage when thickly coated. Increasing the hardness of the coating often leads to increased brittleness and decreased wear resistance and impact resistance. Summary of the Invention

[0006] The purpose of this invention is to provide a high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating and its preparation method, aiming to solve any of the above-mentioned problems and achieve environmental protection, thick coating capability, and thorough curing.

[0007] This invention is mainly achieved through the following technical solutions: A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating comprises, by weight: 30-50 parts of bio-based UV-curing oligomer, 20-40 parts of reactive diluent, 2-5 parts of photoinitiator, 5-15 parts of thermally latent curing agent, 5-20 parts of functional inorganic filler, and 0.5-2 parts of additives; The bio-based UV-curable oligomer is castor oil-based maleic acid half ester modified epoxy acrylate; the heat-latent curing agent includes end-capped isocyanate and thiol compound, and the molar ratio is 1:1 to 1:1.2.

[0008] To better realize the present invention, the product further comprises, by weight, 30 parts of bio-based UV-curable oligomer, 20 parts of reactive diluent, 2 parts of photoinitiator, 5 parts of thermally latent curing agent, 5 parts of functional inorganic filler and 0.5 parts of additives.

[0009] To better realize the present invention, the product further comprises, by weight, 35 parts of bio-based UV-curable oligomer, 25 parts of reactive diluent, 3 parts of photoinitiator, 9 parts of thermally latent curing agent, 10 parts of functional inorganic filler and 1 part of additive.

[0010] To better realize the present invention, the product further comprises, by weight, 45 parts of bio-based UV-curable oligomer, 35 parts of reactive diluent, 4 parts of photoinitiator, 14 parts of thermally latent curing agent, 15 parts of functional inorganic filler and 1.5 parts of additives.

[0011] To better realize the present invention, the product further comprises, by weight, 40 parts of bio-based UV-curable oligomer, 30 parts of reactive diluent, 3.5 parts of photoinitiator, 10 parts of thermally latent curing agent, 12.5 parts of functional inorganic filler and 1.25 parts of additives.

[0012] To better realize the present invention, the product further comprises, by weight, 50 parts of bio-based UV-curable oligomer, 40 parts of reactive diluent, 5 parts of photoinitiator, 15 parts of thermally latent curing agent, 20 parts of functional inorganic filler and 2 parts of additives.

[0013] To better realize the present invention, the thiol compound is pentaerythritol tetra-3-mercaptopropionate.

[0014] To better realize the present invention, the functional inorganic filler further comprises nano-alumina and flake silica with surface modification using silane coupling agent, and the mass ratio is 1:1 to 3:1.

[0015] To better realize the present invention, the photoinitiator further comprises 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

[0016] To better realize the present invention, the active diluent further includes any one or more of trimethylolpropane triacrylate, lauryl acrylate, and bisphenol A diacrylate.

[0017] This invention is mainly achieved through the following technical solutions: A method for preparing a high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating includes the following steps: Step S1: Pre-dispersion: Under light-protected conditions, add the bio-based UV-curable oligomer and reactive diluent to the reactor; stir at 300-500 r / min for 10-15 minutes at 40-50℃. Step S2: Filler impregnation: Add functional inorganic filler to the reactor and increase the stirring speed to 800-1200 r / min, disperse at high speed for 20-30 minutes; Step S3: Adding additives: Reduce the stirring speed to 400-600 r / min, and add the photoinitiator, heat-latent curing agent and additives in sequence, and continue stirring for 30-40 minutes; Step S4: Filtration: The reactants are filtered through a sieve to obtain a photothermal dual-curing, thick-coated wear-resistant coating.

[0018] The beneficial effects of this invention are as follows: (1) This invention combines bio-based UV-curable oligomers, active monomers, and inorganic fillers, along with a combination of UV curing and a heat-induced "click chemistry" reaction (thorough curing of the bottom layer). The resulting coating exhibits three core properties: high hardness, high wear resistance, and the ability to be applied in thick layers. The invention also boasts excellent storage stability: the selected latent heat curing agent does not react at room temperature, ensuring a shelf life of at least 12 months. This invention offers advantages such as high bio-based content and high curing efficiency, making it suitable for thick-film applications. It achieves a balance between deep, thorough curing and excellent mechanical properties, demonstrating good practicality. Specifically, this invention possesses superior thick-film coating and deep curing capabilities, perfectly solving the curing challenges of complex workpieces and thick coatings. It can achieve a dry film thickness of 150-300 μm in a single application without cracking or stickiness.

[0019] (2) This invention uses bio-based UV-curable oligomers as the core film-forming material to build a preliminary three-dimensional network framework for the coating, which can significantly improve the hardness and wear resistance of the coating. Secondly, it significantly reduces the product's dependence on petroleum resources and has extremely low VOC (volatile organic compounds) content, which is in line with the development direction of green chemistry.

[0020] (3) This invention has high hardness and high wear resistance: This invention provides a high cross-linking density foundation through castor oil-based maleic acid half ester modified epoxy acrylate skeleton, and is compounded with modified nano alumina filler, so that the pencil hardness of the coating can reach 4H~6H, and the wear resistance (750g / 500r) ≤15mg. Secondly, this invention has excellent impact resistance: This invention forms a three-dimensional cross-linked network structure through castor oil-based maleic acid half ester modified epoxy acrylate (bifunctional bio-based oligomer), and the sheet silica plays a "skeleton support" role in the coating. The impact strength of the coating can reach more than 50kg·cm, which can effectively resist the damage caused by external mechanical impact. At the same time, the synergistic reaction of the end-capped isocyanate and thiol compound in the heat-latent curing agent further optimizes the uniformity and density of the cross-linked network, so that the stress of the coating can be quickly dispersed when subjected to impact, avoiding the cracking or peeling of the coating caused by stress concentration, thus maintaining high hardness while taking into account excellent impact resistance.

[0021] (4) The coating of the present invention has good flexibility: the long fatty chains of castor oil and the flexible segments formed by the click reaction of thiols give the coating good toughness and adhesion, and it can pass the bending test of a 1mm shaft bar without cracking. The coating of the present invention also has excellent adhesion, and the adhesion level on the surface of substrates such as metal and wood can reach level 0 (cross-cut test). The coating is not easy to fall off during long-term use; its chemical corrosion resistance is also outstanding. It can withstand neutral salt spray for more than 500 hours, and is resistant to immersion in common media such as water, alcohol and machine oil. It can effectively protect the substrate from external erosion and extend the service life of the substrate. Detailed Implementation

[0022] Example 1: A high-hardness, wear-resistant, and thick-coatable bio-based UV-thermal dual-curing coating comprises, by weight: 30-50 parts of a bio-based UV-curable oligomer, 20-40 parts of an reactive diluent, 2-5 parts of a photoinitiator, 5-15 parts of a thermally latent curing agent, 5-20 parts of a functional inorganic filler, and 0.5-2 parts of additives. Preferably, the bio-based UV-curable oligomer is a castor oil-based maleic acid half-ester modified epoxy acrylate, which is a bifunctional acrylated oligomer. The thermally latent curing agent is a composition of a capped isocyanate and a thiol-containing compound, wherein the molar ratio of the capped isocyanate to the thiol-containing compound is 1:1 to 1:1.2.

[0023] The reactive diluent is used to participate in the curing reaction, adjust viscosity, achieve thick coating, and ensure the feasibility of the process; participate in crosslinking to achieve high hardness and wear resistance; balance the system, improve overall performance, and assist in deep light absorption or thermal curing; maintain bio-based properties and ensure the overall renewable carbon content of the coating; specifically, the reactive diluent includes lauryl acrylate and / or bisphenol A diacrylate ethoxylate.

[0024] The photoinitiator absorbs ultraviolet light energy and converts it into chemical energy, instantly initiating the curing reaction of the coating. Specifically, the photoinitiator is a compound of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide. The photoinitiator determines the surface drying speed by initiating curing, controls the curing depth to match the thick coating process, and works synergistically with thermal curing to ensure complete deep curing.

[0025] The latent heat curing agent is used to achieve deep dark-area curing. Because the coating itself blocks ultraviolet light, deep curing is often ineffective. In this case, the latent heat curing agent can be activated during subsequent heating, initiating a cross-linking reaction in the deep layers. It forms a complete and dense three-dimensional network together with the cured surface layer, ensuring the overall hardness and wear resistance of the coating. Specifically, the latent heat curing agent comprises a composition of a capped isocyanate and a thiol-containing compound. The capped isocyanate is used to extend the shelf life of the coating, avoiding the waste caused by the need for fresh preparation in traditional two-component coatings. The thiol compound is pentaerythritol tetra-3-mercaptopropionate. The pentaerythritol tetra-3-mercaptopropionate optimizes the cross-linking structure, improves mechanical strength, increases the cross-linking density and glass transition temperature of the coating, and forms an interpenetrating polymer network structure with the photocurable network. This structure more effectively dissipates external forces, thereby synergistically improving the final hardness and wear resistance of the coating.

[0026] The functional inorganic filler is used to construct a wear-resistant layer, resolve agglomeration, enhance the effect, reduce internal stress, and minimize shrinkage. Specifically, the functional inorganic filler comprises a mixture of nano-alumina modified with a silane coupling agent and lamellar silica, with a mass ratio of nano-alumina to lamellar silica of 1:1 to 3:1. The nano-alumina modified with the silane coupling agent forms a rigid skeleton in the coating, acting like armor to resist scratches and wear. The lamellar silica tends to align in parallel within the coating, forming a layered, fish-scale-like physical barrier that not only reflects crack propagation paths but also effectively blocks the penetration of moisture and corrosive media, acting as a physical shield.

[0027] The additives are used to efficiently synergistically link substances with different properties, such as resins, fillers, and curing agents, to ensure smooth preparation, stable storage, perfect application, and ultimately achieve the designed performance of the coating. Specifically, the additives include wetting and dispersing agents, anti-settling agents, and stabilizers. The wetting and dispersing agents are used to quickly wet filler particles and prevent them from re-aggregating by generating charge repulsion or steric hindrance effects on the particle surface through adsorption. The anti-settling agents are used to establish a thixotropic network to support the filler particles and prevent hard deposition. The stabilizers are used to consume free radicals generated during storage or transportation due to heating or dark reactions, preventing the coating viscosity from increasing or gelling before application.

[0028] The preparation method of the above-mentioned high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating includes the following steps: (1) Pre-dispersion: Under light-protected conditions, the bio-based UV-curable oligomer is first added to the reactor, followed by the reactive diluent. The mixture is dispersed at 300-500 r / min for 10-15 minutes at 40-50°C using a high-speed disperser to ensure thorough mixing. The reaction principle here is primarily free radical copolymerization. Castor oil-based maleic acid half-ester modified epoxy acrylate serves as the main performance "skeleton," while the two reactive diluents respectively regulate hardness and toughness. Under photoinitiation, a unified network is formed through the opening of carbon-carbon double bonds (C=C).

[0029] (2) Filler wetting: Add functional inorganic fillers to the above mixture, increase the stirring speed to 800-1200 r / min, and disperse at high speed for 20-30 minutes to ensure that the fillers are fully wetted and dispersed. The reaction principle here is mainly to construct a "ceramic reinforced network" that is comprehensively upgraded from microstructure to macro performance, and to synergistically solve the performance bottleneck of a single organic coating.

[0030] (3) Adding additives: Reduce the stirring speed to 400-600 r / min, and add the photoinitiator, thermal latent curing agent and additives in sequence. Continue stirring for 30-40 minutes to ensure that the additives are evenly dispersed in the coating system. The reaction principle here is mainly to construct a double cross-linking network through two sequential reactions of photocuring and thermal curing. That is, photocuring is responsible for rapid setting, ensuring "surface dryness" and "hardness"; thermal curing is responsible for deep curing, ensuring "complete dryness" and comprehensive performance.

[0031] (4) Filtration: The resulting mixture is filtered through a 400-mesh sieve to remove any possible impurity particles, resulting in a high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating.

[0032] This invention combines the dual protection of "light" and "heat," while also using more environmentally friendly raw materials. The specific characteristics of this invention are as follows: 1) This invention overcomes the problems of "shading" and "thick coating"; Traditional UV-curable coatings rely entirely on ultraviolet light for curing, which has two major drawbacks: shaded areas where light doesn't reach will not cure; and when the coating is too thick, the underlying layers will not cure completely due to light attenuation. However, this invention introduces a thermal initiator, which allows for secondary polymerization in the deeper layers or shaded areas of the coating after UV irradiation, achieving "surface drying under light and thorough drying under heat," fundamentally solving the problems of cracking and poor adhesion in thick coatings.

[0033] 2) The present invention has a wide range of construction applications; the present invention can achieve thick coating (up to 200μm or even thicker), and is suitable for three-dimensional workpieces with complex depressions. At the same time, it also provides more flexible thermosetting connection options on the production line.

[0034] 3) The raw materials of the present invention are more sustainable; the main film-forming substance (castor oil-based maleic acid half ester modified epoxy acrylate) and active diluent of the present invention are extracted from biomass such as castor oil and soybean oil, and their bio-based carbon content can usually reach more than 20%-50%, which greatly reduces the dependence on petroleum resources.

[0035] 4) This invention combines rigidity and flexibility. Through a dual-cured interpenetrating network, it maintains not only high hardness but also better flexibility due to the long-chain characteristics of the bio-based structure. Simultaneously, combined with nano-abrasion-resistant fillers, it surpasses traditional formulations in abrasion resistance. The bio-based UV-curable oligomers primarily play a framework and foundational role in this coating system, fundamentally determining the final hardness, abrasion resistance, adhesion, and bio-based content of the coating.

[0036] Example 2: A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating comprises, by weight: 30 parts castor oil-based maleic acid half ester modified epoxy acrylate, 20 parts reactive diluent (trimethylolpropane tripropylene ester TMPTA), 2 parts photoinitiator (a compound of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide), 5 parts thermal latent curing agent (the molar ratio of end-capped isocyanate to thiol-containing compound is 1:1 to 1:1.2), 5 parts functional inorganic filler (nano-alumina and flake silica surface-modified with silane coupling agent KH-570, with a mass ratio of 1:1 to 3:1), and 0.5 parts wetting and dispersing agent.

[0037] The preparation method of the high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating includes the following steps: First, under light-protected conditions, the bio-based UV-curable oligomer and reactive diluent are added to the reactor and stirred at 400 r / min for 11 minutes at 44°C until they are evenly mixed. Then, slowly add the functional inorganic filler, increase the rotation speed to 1000 r / min, and disperse at high speed for 25 minutes to ensure that the filler is fully wetted and dispersed.

[0038] Next, reduce the rotation speed to 500 r / min, add the photoinitiator, thermal latent curing agent and additives in sequence, stir continuously for 35 minutes, and finally filter through a 400 mesh sieve.

[0039] Example 3: A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating comprises, by weight: 35 parts castor oil-based maleic acid half ester modified epoxy acrylate, 25 parts reactive diluent (trimethylolpropane tripropylene ester TMPTA), 3 parts photoinitiator (a compound of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide), 9 parts thermal latent curing agent (a molar ratio of end-capped isocyanate to thiol-containing compound of 1:1 to 1:1.2), 10 parts functional inorganic filler (nano-alumina and flake silica surface-modified with silane coupling agent KH-570, with a mass ratio of 1:1 to 3:1), and 1 part wetting and dispersing agent.

[0040] The preparation method of the high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating includes the following steps: First, under light-protected conditions, the bio-based UV-curable oligomer and reactive diluent are added to the reactor and stirred at 400 r / min for 11 minutes at 44°C until they are evenly mixed. Then, slowly add the functional inorganic filler, increase the rotation speed to 1000 r / min, and disperse at high speed for 25 minutes to ensure that the filler is fully wetted and dispersed.

[0041] Next, reduce the rotation speed to 500 r / min, add the photoinitiator, thermal latent curing agent and additives in sequence, stir continuously for 35 minutes, and finally filter through a 400 mesh sieve.

[0042] Example 4: A high-hardness, wear-resistant, and thick-coatable bio-based UV-thermal dual-curing coating, comprising, by weight: 45 parts castor oil-based maleic acid half ester modified epoxy acrylate, 35 parts reactive diluent (trimethylolpropane tripropylene ester TMPTA), 4 parts photoinitiator (a compound of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide), 14 parts heat-latent curing agent (molar ratio of end-capped isocyanate to thiol compound of 1:1 to 1:1.2), 15 parts functional inorganic filler (nano-alumina and flake silica surface modified with silane coupling agent KH-570, with a mass ratio of 1:1 to 3:1), and 1.5 parts wetting and dispersing agent.

[0043] The preparation method of the high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating includes the following steps: First, under light-protected conditions, the bio-based UV-curable oligomer and reactive diluent are added to the reactor and stirred at 400 r / min for 11 minutes at 44°C until they are evenly mixed. Then, slowly add the functional inorganic filler, increase the rotation speed to 1000 r / min, and disperse at high speed for 25 minutes to ensure that the filler is fully wetted and dispersed.

[0044] Next, reduce the rotation speed to 500 r / min, add the photoinitiator, thermal latent curing agent and additives in sequence, stir continuously for 35 minutes, and finally filter through a 400 mesh sieve.

[0045] Example 5: A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating comprises, by weight: 40 parts castor oil-based maleic acid half ester modified epoxy acrylate, 30 parts reactive diluent (trimethylolpropane tripropylene ester TMPTA), 3.5 parts photoinitiator (a compound of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide), 10 parts thermal latent curing agent (the molar ratio of end-capped isocyanate to thiol-containing compound is 1:1 to 1:1.2), 12.5 parts functional inorganic filler (nano-alumina and flake silica surface modified with silane coupling agent KH-570, with a mass ratio of 1:1 to 3:1), and 1.25 parts wetting and dispersing agent.

[0046] The preparation method of the high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating includes the following steps: First, under light-protected conditions, the bio-based UV-curable oligomer and reactive diluent are added to the reactor and stirred at 400 r / min for 11 minutes at 44°C until they are evenly mixed. Then, slowly add the functional inorganic filler, increase the rotation speed to 1000 r / min, and disperse at high speed for 25 minutes to ensure that the filler is fully wetted and dispersed.

[0047] Next, reduce the rotation speed to 500 r / min, add the photoinitiator, thermal latent curing agent and additives in sequence, stir continuously for 35 minutes, and finally filter through a 400 mesh sieve.

[0048] Example 6: A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating comprises, by weight: 50 parts castor oil-based maleic acid half ester modified epoxy acrylate, 40 parts reactive diluent (trimethylolpropane tripropylene ester TMPTA), 5 parts photoinitiator (a compound of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide), 15 parts thermal latent curing agent (a molar ratio of end-capped isocyanate to thiol-containing compound of 1:1 to 1:1.2), 20 parts functional inorganic filler (nano-alumina and flake silica surface-modified with silane coupling agent KH-570, with a mass ratio of 1:1 to 3:1), and 2 parts wetting and dispersing agent.

[0049] The preparation method of the high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating includes the following steps: First, under light-protected conditions, the bio-based UV-curable oligomer and reactive diluent are added to the reactor and stirred at 400 r / min for 11 minutes at 44°C until they are evenly mixed. Then, slowly add the functional inorganic filler, increase the rotation speed to 1000 r / min, and disperse at high speed for 25 minutes to ensure that the filler is fully wetted and dispersed.

[0050] Next, reduce the rotation speed to 500 r / min, add the photoinitiator, thermal latent curing agent and additives in sequence, stir continuously for 35 minutes, and finally filter through a 400 mesh sieve.

[0051] Comparative Example 1: An ultraviolet-curable coating, by weight, comprises: 30 parts of commercially available ordinary epoxy acrylate, 20 parts of reactive diluent (trimethylolpropane tripropylene ester, TMPTA), 2 parts of photoinitiator (a compound of 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide), and 0.5 parts of wetting and dispersing agent.

[0052] The method for preparing the ultraviolet-curable coating includes the following steps: First, under light-protected conditions, ordinary epoxy acrylate and reactive diluent are added to the reaction vessel and stirred at 400 r / min for 11 minutes at 44°C until they are mixed evenly. Next, adjust the rotation speed to 500 r / min, add the photoinitiator and additives in sequence, stir continuously for 35 minutes, and finally filter through a 400 mesh sieve.

[0053] The coatings prepared in Examples 2, 3, 4, 5 and 6, as well as the conventional UV-curable coating prepared in Comparative Example 1, were subjected to performance tests. As shown in Table 1, the coatings prepared in Examples 2, 3, 4, 5 and 6 outperformed the conventional UV-curable coatings in terms of hardness, abrasion resistance, VOC content, flexibility, coating thickness, adhesion and drying time, demonstrating significant advantages.

[0054] Table 1

[0055] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Any simple modifications or equivalent changes made to the above embodiments based on the technical essence of the present invention shall fall within the protection scope of the present invention.

Claims

1. A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating, characterized in that, The product comprises, by weight, 30-50 parts of bio-based UV-curable oligomer, 20-40 parts of reactive diluent, 2-5 parts of photoinitiator, 5-15 parts of thermally latent curing agent, 5-20 parts of functional inorganic filler, and 0.5-2 parts of additives. The bio-based UV-curable oligomer is castor oil-based maleic acid half ester modified epoxy acrylate; the heat-latent curing agent includes end-capped isocyanate and thiol compound, and the molar ratio is 1:1 to 1:1.

2.

2. The high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to claim 1, characterized in that, The product comprises, by weight, 30 parts of bio-based UV-curable oligomer, 20 parts of reactive diluent, 2 parts of photoinitiator, 5 parts of thermally latent curing agent, 5 parts of functional inorganic filler, and 0.5 parts of additives.

3. The high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to claim 1, characterized in that, The product comprises, by weight, 35 parts bio-based UV-curable oligomer, 25 parts reactive diluent, 3 parts photoinitiator, 9 parts thermally latent curing agent, 10 parts functional inorganic filler, and 1 part additive.

4. The high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to claim 1, characterized in that, The product comprises, by weight, 45 parts of bio-based UV-curable oligomer, 35 parts of reactive diluent, 4 parts of photoinitiator, 14 parts of thermally latent curing agent, 15 parts of functional inorganic filler, and 1.5 parts of additives.

5. The high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to claim 1, characterized in that, The product comprises, by weight, 40 parts of bio-based UV-curable oligomer, 30 parts of reactive diluent, 3.5 parts of photoinitiator, 10 parts of thermally latent curing agent, 12.5 parts of functional inorganic filler, and 1.25 parts of additives.

6. The high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to claim 1, characterized in that, The product comprises, by weight, 50 parts of bio-based UV-curable oligomer, 40 parts of reactive diluent, 5 parts of photoinitiator, 15 parts of thermally latent curing agent, 20 parts of functional inorganic filler, and 2 parts of additives.

7. A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to any one of claims 1-6, characterized in that, The thiol compound is pentaerythritol tetra-3-mercaptopropionate.

8. A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to any one of claims 1-6, characterized in that, The functional inorganic filler includes nano-alumina and flake silica with surface modification using silane coupling agent, and the mass ratio is 1:1 to 3:

1.

9. A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to any one of claims 1-6, characterized in that, The photoinitiator includes 1-hydroxycyclohexylphenyl ketone and 2,4,6-trimethylbenzoyl-diphenylphosphine oxide.

10. A high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating according to any one of claims 1-6, characterized in that, The reactive diluent includes any one or more of trimethylolpropane triacrylate, lauryl acrylate, and bisphenol A diacrylate.

11. A method for preparing a high-hardness, wear-resistant, and thick-coated bio-based UV-thermal dual-curing coating as described in any one of claims 1-10, characterized in that, Includes the following steps: Step S1: Pre-dispersion: Under light-protected conditions, add the bio-based UV-curable oligomer and reactive diluent to the reaction vessel; Stir at 300-500 r / min for 10-15 minutes at 40-50℃; Step S2: Filler impregnation: Add functional inorganic filler to the reactor and increase the stirring speed to 800-1200 r / min, disperse at high speed for 20-30 minutes; Step S3: Adding additives: Reduce the stirring speed to 400-600 r / min, and add the photoinitiator, heat-latent curing agent and additives in sequence, and continue stirring for 30-40 minutes; Step S4: Filtration: The reactants are filtered through a sieve to obtain a photothermal dual-curing, thick-coated wear-resistant coating.